Hydrothermal analysis of magneto hydrodynamic nanofluid flow between two parallel by AGM. (September 2019) - Derakhshan, R.; Shojaei, Ahmadreza; Hosseinzadeh, Kh; Nimafar, M.; Ganji, D.D.
Abstract: In this paper, heat and mass transfer process of steady nanofluid flow between two parallel plates is investigated in existence of uniform magnetic field. The impact of thermophoresis and Brownian motion has been considered in the model of nanofluid. Akbari-Ganji's Method (AGM) is selected for solving governing equations. Results have been compared with numerical method (Runge–Kutte 4th) in order to verify the correctness of the AGM. The analysis is carried out for various active parameters such as: Magnetic parameter, viscosity coefficient, thermophoretic parameter and Brownian parameter. Results indicate that Nusselt number decreases with augments of thermophoretic and Brownian parameters while opposite trend are observed for viscosity coefficient. Also concentration of nanofluid decreases when Brownian motion increases while it enhances with augments of thermophoretic parameter.